PENGARUH SKILL, PELATIHAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PKS PTPN V SEI GARO KABUPATEN KAMPAR - Supardi Supardi (STIE Bangkinang Publishing, 2019)
The purpose of this study was to determine the effect of skill, training and competence on the performance of employees in the PKS PTPN V Sei Garo kampar Regency. The population in this study were 94 employees and the entire population was sampled so that the technique in this study used cencus techniques. As for data analysis carried out by multiple linear regression models. Based on the simulthan test of the study it can be concluded that skill, training and competence affect the performance of employees in the PKS PTPN V Sei Garo kampar Regency. Based on partial results it is know that the skill variable is more dominantly influencing on the performance of employees in the PKS PTPN V Sei Garo Kampar Regency. While the contribution of skill, training and competence variables to the performance of emplooyes variables is strong with equal to 61,9% while the remaining 38,1% is influenced by other variables not examined in this study.